HARAPAN MAHASISWA BERPERILAKU WARIA DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN (FKIP) UNIVERSITAS RIAU - Sri Wulandari; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the expectations of transgender studentbehavior in the Teaching and Education Faculty (FKIP), Riau University. Theformulation of the problem in this study is what are the expectations of studentsbehaving transgender in the Faculty of Teacher Training and Education (FKIP),University of Riau? This type of research is descriptive with a qualitative approach. Theresults of the research on the expectations of students behaving transgender at theFaculty of Teacher Training and Education (FKIP), University of Riau are seen from 4indicators, namely (1) Expectations for achievement results seen from praise, bonusesor prizes, and environmental reactions, which is the hope of students behavingtransgender people is praise and good environmental reaction to him. The praiseobtained makes students behave more enthusiastically by transgender people, feelappreciated by those around them, (2) Expectations for dignity / value (valence) as seenfrom, the strength and behavior of students who behave transgender people want to berespected and easily interact with everyone even though they are transgender. different,so that they can be polite to everyone, (3) Expectations of business achievement seenfrom studying diligently and the opportunities for students who have transgenderbehavior are wanting to get along easily with people, especially with female friends, (4)Expectations of future orientation are seen from educational orientation, workorientation and family orientation. Students who behave wariabare hope that thedesired goals can be achieved even though they are not in accordance with theirmajors, and their families pay more attention and care to them, so that their educationis better.Key Words: Expectations of students behaving waria